A new twist to Sin3 complexes in pluripotent cells. (28th June 2017) - Pantier, Raphaël; Mullin, Nicholas P; Chambers, Ian
Abstract : Sin3a is a central component of a class of histone deacetylase‐containing transcriptional co‐regulatory complexes. In this issue of The EMBO Journal, Streubel et al (2017 ) purify Sin3a and identify a variant Sin3a complex containing Fam60a in undifferentiated embryonic stem cells (ESCs). Fam60a is a critical component of the ESC Sin3a complex since Fam60a knockdown leads to an extended G1 cell cycle phase and reduced ESC self‐renewal. These exciting results open up new questions about how biochemical differences between variant Sin3a complexes may facilitate alterations in cell‐specific function. Abstract : The discovery of a stem cell‐specific Sin3a‐HDAC subunit required for self‐renewal suggests that chromatin modifying complexes may exist in a variety of cell type‐dependent forms.